Combinatorial Study of the Si-Sn-O System as Negative Electrode Materials in Li-Ion Cells. Issue 2 (17th November 2015) - Zhao, Xiuyun; Schreiber, M. T.; MacEachern, L.; Sanderson, R. J.; Dunlap, R. A.; Obrovac, M. N.
Abstract : Six Sny O1-x-y films with 0.45 < x < 0.80, 0.05 < y < 0.35, and 0.05 < (1-x-y) < 0.40 have been prepared using a magnetron sputtering method. All compositions had an amorphous structure and good capacity retention. Reversible volumetric capacities exceeding 2000 Ah/L were obtained in films with high Si or Sn content. The initial coulombic efficiency becomes reduced when the oxygen content is increased, as increasing the oxygen content in these films causes a reduction in reversible capacity. Surprisingly, however, the oxygen content does not substantially increase the irreversible capacity. Further work should focus on improving the initial coulombic efficiency of Si-Sn-O electrodes.